Beneficial role of antioxidants during liver transplantation - Vaishali S. Patil; Adinath N. Suryakar; Pradeep Naik (Al Ameen Medical College, 2014)
Background & Objectives: Initial graft dysfunction, an event mainly due to the unavoidable ischemia-reperfusion (I/R) injury of the transplanted organ, is one of the most important early post-operative problems in liver transplantation. It is well known that antioxidants significantly improves early allograft function and both graft and patient survival. Thus, the present study was carried out to evaluate the exact role of antioxidants during liver transplantation. Method: We assessed serum lipid peroxide (as oxidant), serum superoxide dismutase (SOD) and serum vitamin E (as antioxidant) in 30 patients undergoing liver transplantation and equal numbers of healthy subjects. Results: We found that the concentration of serum lipid peroxide (MDA) was significantly increased and antioxidants were significantly decreased in all stages of liver transplant patients as compared with healthy controls (P<0.001). On reperfusion there was pronounced consumption of antioxidants and highly elevated levels of serum lipid peroxide was seen than in those of pre-reperfusion and post-reperfusion stages (P<0.0001) of liver transplantations. Conclusion: Antioxidants can be used in liver transplantation patients to effectively reduce the severity of reperfusion injury and to improve short-term allograft function and patient survival.